Talent Recruiting Innovations and High Start-Ups - Sehar Shahzad Farooq; Irfan Mehmood; Soon Ki Jung (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
The talent management market is increasing rapidly, and the software and platform part of the market consists of recruitment tools, job interviewing tools, social media advertising, assessments, and Artificial Intelligence (AI) based systems [1]. The growth in talent recruiting is driven by the recent innovations in AI such as deep learning and convolutional neural networks [2].